OVERCOMING CHALLENGES OF SETTING-UP A LARGE AND COMPLEX PRE-HOSPITAL TRIAL: AIRWAYS-2. Issue 9 (18th August 2016) - Robinson, Maria; Taylor, Jodi; Voss, Sarah; Rogers, C; Brett, S; Benger, Jonathan
Abstract : Background: AIRWAYS-2 is an NIHR-funded study to determine the best initial approach to advanced airway management during out of hospital cardiac arrest (OHCA). The trial will enrol more than 9, 000 patients and 1, 500 paramedics. To achieve this, collaboration between four Ambulance Trusts and every hospital served by these was required. Patients receive the trial intervention pre-hospital, and the primary outcome and other data are collected in-hospital. We describe the set-up process for this large, complex, pre-hospital trial. Methods: Pre-hospital research presents unique challenges. Obtaining approvals and set-up can be complex, time consuming and expensive. A strategy to engage with all stakeholders was developed, ensuring that they were well informed during the planning and set-up phases. Specifically, this included: establishing R&D and Clinical Research Network contacts; involving critical care leads; consultation with ambulance trusts; utilisation of network support; implementation of a wide-reaching communications plan. All hospitals were contacted to identify local collaborators prior to SSI submission, and were provided with FAQs and study information. The approval process was streamlined. The SSI was generic and did not require input from local teams. A one page statement of responsibilities replaced review of contracts for sites. Comprehensive review by REC & CAG meant that full consideration was given to the ethical challenges during planning and set-up phases. Results: Trust permission was obtained from all acute hospitals (95 in total), served by participating ambulance trusts. All set-up milestones were achieved and the first patient was enrolled on time. Conclusions: Ambulance services are increasingly research active. Incidents attended can be life-threatening emergencies but good quality pre-hospital trials are possible. Early and comprehensive engagement assists with sites' participation and enables successful set-up of collaborative trials.